Inadequate supply of fuelwood and timber from forests of Nepal - Shrestha, Raj Bahadur (Banko Janakari, 2017)
The existing public supply of fuelwood does not meet the demand of growing population. While peoples' need of fuelwood is being met mostly from government forests legally or illegally, and some from community and private lands, the government will soon find it difficult to compensate 69% of fuelwood energy from the depleting forest. Appropriate technologies such as biogass, improved stoves, etc. should be promoted to reduce fuelwood consumption. Also, appropriate harvesting technology could help improve fuelwood and timber supply system of the country.